POTRET MISKONSEPSI SISWA KELAS IV SDN KEPANJENLOR 3 BLITAR PADA MATERI SIKLUS HIDUP HEWAN - Nur Hanifatun Nadhif; Candra Utama (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The purpose of this study was to determine the level of misconceptions portraits of fourth grade students at SDN Kepanjenlor 3 Blitar on the material life cycle of animals. This research is aqualitative research with a descriptive approach. The sample of this study were 6 grade IV students of SDN Kepanjenlor 3 Blitar. The data collection technique is to give a test in the form of essay questions. The results of this study were found that there were misconceptions in three sub-concepts, namely in the sub-concept of animal life cycle types, a misconception percentage of 27% was obtained, in the sub-concept of animal life cycle stages, a misconception percentage was obtained by 46%, and in the sub-concept of life cycle examples In animals, the percentage of misconceptions was 46%.